Upaya mewujudkan Sustainable Development Goals (SDGs) di Indonesia melalui optimalisasi manajemen celah pajak pada perusahaan energi - Setiawan, Audita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study examines how energy tax loopholes in Indonesia can be a solution for mandatory companies such as energy companies to minimize the tax burden borne but still comply with applicable tax regulations. Descriptive research is research used by researchers in this study. Researchers describe facts, data, and information obtained from literature studies such as books, and journals to research results related to the research topic. In this study, it is explained that some several impacts or effects are felt when the company as a taxpayer takes illegal actions such as tax evasion in tax planning. One of them is very influential on the tax funds received by the government which will be used to carry out sustainable development in Indonesia. Therefore, companies need to increase their knowledge of tax provisions so that they can find legal solutions to minimize the tax burden they bear, such as through loopholes and various fiscal and tax policies by the government such as tax allowances and tax holidays. Through this solution, it is hoped that the company will not feel burdened by its tax burden so that sustainable development in Indonesia can be realized.